Factors influencing termination of employment in Malaysian private sector: an analysis from industry - Othman, Noraishah; Mat, Zawiah; Ismail, Norain (Philstat, 2022)
Purpose of the study: This paper aims to analyse the factors of employment termination in Malaysian Private Sector from the industry.